2015
DOI: 10.1158/1078-0432.ccr-14-3022
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Leukemia Eradication by Combined Treatment with Retinoic Acid and HIF Inhibition by EZN-2208 (PEG-SN38) in Preclinical Models of PML-RARα and PLZF-RARα–Driven Leukemia

Abstract: Purpose: Retinoic acid-arsenic trioxide (ATRA-ATO) combination therapy is the current standard of care for patients with acute promyelocytic leukemia (APL) carrying the oncogenic fusion protein PML-RARa. Despite the high cure rates obtained with this drug combination, resistance to arsenic is recently emerging. Moreover, patients with APL carrying the PLZF-RARa fusion protein are partially resistant to ATRA treatment. Hypoxia-inducible factor-1a (HIF-1a) activation has been recently reported in APL, and EZN-22… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…However, the classification may not be accurate, because some agents target more than one mechanism and it may be inappropriate to include them in a definite category. The targets and mechanisms of HIF inhibitors (Table 1) and some evaluated in clinical trials [Data were obtained from National Clinical Trial (https://clinicaltrials.gov)] are summarized 3031323334353637383940414243444546474849505152535455…”
Section: Hif Inhibitors For Cancer Therapymentioning
confidence: 99%
“…However, the classification may not be accurate, because some agents target more than one mechanism and it may be inappropriate to include them in a definite category. The targets and mechanisms of HIF inhibitors (Table 1) and some evaluated in clinical trials [Data were obtained from National Clinical Trial (https://clinicaltrials.gov)] are summarized 3031323334353637383940414243444546474849505152535455…”
Section: Hif Inhibitors For Cancer Therapymentioning
confidence: 99%
“…L-ascorbic acid was also able to specifically inhibit the proliferation of human CML cells via downregulation of HIF-1α transcription [135]. EZN-2968, a small 3 rd generation antisense oligonucleotide against HIF1A mRNA, delayed acute promyelocytic leukaemia (APL) and MM progression [160, 161]. EZN-2968 has also been reported to block the interaction between MM cells and BM stromal cells through HIF-1α inhibition [161].…”
Section: Hypoxia And/or Hifs As Targets To Treat Hmsmentioning
confidence: 99%
“…EZN-2968 has also been reported to block the interaction between MM cells and BM stromal cells through HIF-1α inhibition [161]. Furthermore, the combination of EZN-2088, a polyethylene glycol conjugate of irinotecan (PEG-SN38), with all-trans retinoic acid (ATRA) synergized to eradicate preclinical models of PML-RARα (promyelocytic leukaemia protein-retinoic receptor antagonist alpha) and PLZF (promyelocytic leukaemia zinc finger)-RARα-driven leukaemia [160]. More recently, it has been shown that chetomin, a small molecule able to disrupt HIF-1α binding to the p300 coactivator, exhibited antitumor activity in primary MM cells from patients [162].…”
Section: Hypoxia And/or Hifs As Targets To Treat Hmsmentioning
confidence: 99%
“…EZN-2208 (pegylated SN38) has also been shown to inhibit the expression and transcriptional activity of HIF-1α in APL. 59 None of these molecules target HSCs. Another molecule, TH-302, is a hypoxia-activated prodrug that has been reported to preferentially decrease proliferation, reduce HIF-1α expression and induce cell-cycle arrest in AML cells.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%